Non-Accounting Drivers of Forensic Accounting Techniques: Insights from PLS-SEM Analysis - DIWAKAR, Richa; WADHWA, Ritu; RAMAN, T.V.; SRIVASTAVA, Anubha; SHANKAR, R. GOWRI; JAIN, Piyush Kumar (Theoretical and Practical Research in Economic Fields, 2025)
Forensic accounting techniques are pivotal in combating financial fraud and enhancing corporate governance. According to Forensic Accounting Theory, both accounting and non-accounting factors influence the intention to adopt these techniques. This study explores the impact of key non-accounting factors i.e. Bonus Contract, Anonymity, and Collapse Avoidance on adoption of forensic accounting techniques by the practitioners, employing Partial Least Squares Structural Equation Modeling (PLS-SEM) and SmartPLS software. Data was collected from professionals across diverse industries utilising forensic accounting services. The results reveal that these non-accounting factors exert varying levels of influence on adoption intentions. This research enriches the existing body of knowledge by offering new perspectives on the role of non-accounting drivers in forensic accounting adoption, providing actionable insights for policy-makers, regulators, and corporate leaders.